Interpenetrated N-rich MOF derived vesicular N-doped carbon for high performance lithium ion battery. Issue 20 (9th May 2022) - Zhao, Yun-Xiu; Sun, Yuan-Wei; Li, Jun; Wang, Su-Na; Li, Da-Cheng; Dou, Jian-Min; Zhong, Ming; Ma, Hui-Yan; Li, Yun-Wu; Xu, Li-Qiang
Abstract : MOF-derived vesicle-like N-doped carbon presents high reversible capacity, high rate capability and ultralong cycle life as LIB anode. Theoretical calculation verifies the experimental results. Abstract : High-performance lithium ion batteries (LIBs) juggling high reversible capacity, excellent rate capability and ultralong cycle stability are urgently needed for all electronic devices. Here we report employing a vesicle-like porous N-doped carbon material (abbr. N/C-900) as a highly active anode for LIBs to balance high capacity, high rate and long life. The N/C-900 material was fabricated by pyrolysis of a designed crystal MOF LCU-104, which exhibits a graceful two-fold interpenetrating structural feature of N-rich nanocages {Zn6 (dttz)4 } linked through an N-donor ligand bpp (H3 dttz = 4, 5-di(1 H -tetrazol-5-yl)-2 H -1, 2, 3-triazole, bpp = 1, 3-bis(4-pyridyl)propane). The features of LCU-104 combine high N content (35.1%), interpenetration, and explosive characteristics, which endow the derived N/C material with optimized N-doping for tuning its chemical and electronic structure, a suitably thicker wall to enhance its stability, and a vesicle-like structure to improve its porosity. As an anode material for LIBs, N/C-900 delivers a highly reversible capacity of ca. 734 mA h g −1 at a large current density of 1 A g −1 until the 2000th cycle, revealing its ultralong cycle stability and excellent rate capability. The unique structure and preferential interaction between abundant pyridinic N active sites and Li atoms are responsible for the improved excellent lithium storage capacity and durability performances of the anode according to analysis of the results of computational modeling.